Diário de crise : do naufrágio ao renascimento - Santos, Roberson Rosa dos (2015)
The present thesis part of an interest in research the relationship between the gender of diaries and the writing of people in crisis. It aims to identify the process of diary writing developed during a personal crisis, in other words, to map and follow the meeting between the diary and an individual in a critical condition. For this, we resumed the possibles origins and socio-historical influences of diary gender, starting from navigation diaries towards to critical studies of scholars like Philippe Lejeune, Manuel Alberca, Alain Girard, Béatrice Didier, among others. After a conceptual and cultural reading about the diary gender, this study approaches the use of this support as a transitional object of a crisis. For that, we resort to studies of Donald Winnicott, Ortega y Gasset and Paul Ricoeur to elaborate positions that map the process of crisis in diaries. The positions that we developed are: Wreck position, Anchoring position, Enchantment position and Renaissance position. These positions were developed from reading of diaries of crisis written in mental health services. In this study, the diaries of Lima Barreto and Maura Lopes Cançado, produced during psychiatric hospitalizations, are used as the basis for statement of positions.